A coded aperture microscope for X‐ray fluorescence full‐field imaging. (21st October 2020) - Siddons, D. P.; Kuczewski, A. J.; Rumaiz, A. K.; Tappero, R.; Idir, M.; Nakhoda, K.; Khanfri, J.; Singh, V.; Farquhar, E. R.; Sullivan, M.; Abel, D.; Brady, D. J.; et al.
Abstract : First results from a 10 µm MURA coded aperture optic for a full‐field X‐ray fluorescence microscope are presented. Abstract : The design and construction of an instrument for full‐field imaging of the X‐ray fluorescence emitted by a fully illuminated sample are presented. The aim is to produce an X‐ray microscope with a few micrometers spatial resolution, which does not need to scan the sample. Since the fluorescence from a spatially inhomogeneous sample may contain many fluorescence lines, the optic which will provide the magnification of the emissions must be achromatic, i.e. its optical properties must be energy‐independent. The only optics which fulfill this requirement in the X‐ray regime are mirrors and pinholes. The throughput of a simple pinhole is very low, so the concept of coded apertures is an attractive extension which improves the throughput by having many pinholes, and retains the achromatic property. Modified uniformly redundant arrays (MURAs) with 10 µm openings and 50% open area have been fabricated using gold in a lithographic technique, fabricated on a 1 µm‐thick silicon nitride membrane. The gold is 25 µm thick, offering good contrast up to 20 keV. The silicon nitride is transparent down into the soft X‐ray region. MURAs with various orders, from 19 up to 73, as well as their respective negative (a mask where open and closed positions are inversed compared with the original mask), have been made. Having both signs of mask will reduce near‐field artifacts and make it possible to correct for any lack of contrast.